2010
DOI: 10.1101/gr.111070.110
|View full text |Cite
|
Sign up to set email alerts
|

Global impact of RNA polymerase II elongation inhibition on alternative splicing regulation

Abstract: The rate of RNA polymerase II (Pol II) elongation can influence splice site selection in nascent transcripts, yet the extent and physiological relevance of this kinetic coupling between transcription and alternative splicing (AS) is not well understood. We performed experiments to perturb Pol II elongation and then globally compared AS patterns with genome-wide Pol II occupancy. RNA binding and RNA processing functions were significantly enriched among the genes with Pol II elongation inhibition-dependent chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
210
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(238 citation statements)
references
References 71 publications
16
210
1
3
Order By: Relevance
“…As expected from previous studies and from its ability to inhibit transcription elongation [20][21][22] , CPT favored inclusion more often than exclusion of cassette exons (Fig. 1c).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…As expected from previous studies and from its ability to inhibit transcription elongation [20][21][22] , CPT favored inclusion more often than exclusion of cassette exons (Fig. 1c).…”
Section: Resultssupporting
confidence: 63%
“…Thus, cell responses to DNA damage may involve the coordinated regulation of both nuclear and cytoplasmic sets of transcripts by HuR. Large-scale regulation of alternative polyadenylation and splicing are increasingly involved in cellular processes, including proliferation and genotoxic responses, respectively [1][2][3][4][5][6][7][8]16,[19][20][21] . In this context, our data provide several advances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, reduction of RNAPII elongation rate with CPT or DRB led to the expected increase of alternative exon inclusion. 30 On the other hand, use of RNAPII mutants that have either faster or slower elongation rates yielded alternative splicing changes in both directions, i.e., increase and decrease of inclusion of alternative exons. 31 It also be noted that a recent study demonstrated that slower transcriptional elongation led to increased skipping of an alternative exon instead of the expected increased inclusion, through recruiting a splicing silencer protein to its target sequence on the pre-mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent reports show that the splicing efficiency of specific subsets of transcripts changes in different environmental conditions 12 or when splicing-related proteins are mutated. 13,14 Mutations that alter transcription elongation rates or treatment with drugs that affect transcription can change alternative splicing outcomes in metazoa [15][16][17][18][19][20] and splicing efficiency in yeast. 8,21,22 For example, splicing of the DYN2 alternative splicing reporter pre-mRNA in S. cerevisiae changes when transcription elongation is slowed using the small molecules 6-Azauracil or mycophenolic acid, or by mutating the RNA Pol II subunit Rpb2.…”
Section: Introductionmentioning
confidence: 99%